Rosella Petal Extract (Hibiscus sabdariffa Linn.) as a Reducing Agent in Silver Nanoparticle Synthesis and Its Antibacterial Activity - Dewi Dwi Purwati; Gusrizal Gusrizal; Endah Sayekti (Jurnal Kimia Sains dan Aplikasi, 2023)
Silver nanoparticles have superior properties that attract much attention because they can increase their effectiveness and efficiency compared to their macroscopic size. Silver nanoparticles have several benefits, one of which is as an antibacterial agent. Synthesis of silver nanoparticles was carried out by reducing silver ions (Ag+) to uncharged silver (Ag0) using a reducing agent from Hibiscus sabdariffa Linn. petal extract. This research aims to synthesize silver nanoparticles by studying several parameters that influence their formation, such as the pH of Hibiscus sabdariffa Linn. petal extract, reaction time, silver nitrate concentration, and Hibiscus sabdariffa Linn. petal extract concentration. The silver nanoparticles formed were then tested for their antibacterial activity. The experimental results showed that the best synthesis was performed using Hibiscus sabdariffa Linn. petal extract with pH 10, reaction time of 45 minutes, silver nitrate concentration of 1×10-4 M, and Hibiscus sabdariffa Linn. petal extract concentration of 0.004%. The synthesized silver nanoparticles, examined through a transmission electron microscope, exhibited a size distribution ranging from 2 to 26 nm with an average size of 12 ± 3 nm, which was stable with a storage time of 3 months. Silver nanoparticles showed antibacterial activity against Staphylococcus aureus. Hibiscus sabdariffa Linn. petal extract is a promising reducing agent for producing antibacterial silver nanoparticles, showcasing its potential in this application.